Analisis Yuridis Implementasi Artificial Intelligent Dalam Praktek Kenotariatan - Susilo, Dessy; Dananjaya, Nyoman Satyayudha (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 8 No 02 (2023), 2023)
The purpose of this study is to analyze how the application of cyber notary in the form of Artificial Intelligence in notary practices is contrary to the principles of the Tabellions Officium Fideliter Exercebo and the authenticity of the deed shifts when an electronic deed takes place . The normative juridical method is carried out using a statutory approach and a conceptual approach with primary legal sources, namely the Law on Notary Offices, secondary legal sources from scientific papers and journals and tertiary legal sources from books and seminars. The results od this study found that the application of artificial intelligence in the concept od cyber notary has not provided legal certainty for the users of notary services, this is because the legal umbrella that covers them is in conflict with one another and when applied in notary practice the products produced by notaries become inauthentic or under hand .